The Effectiveness of Writing Relay in Teaching Writing Narrative Text - Hasni, Hasni (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This classroom action research aimed to investigate the effectiveness of utilizing Writing Relay as a teaching method to enhance students' writing skills in narrative text. The study was conducted with eighth-grade students from the 8A Class at SMP Yapis Teminabuan, comprising a total of 23 participants. The research design employed a cyclic process of implementation and assessment to observe the progress of students' writing abilities throughout the intervention. The initial diagnostic test revealed a mean score of 63.98, indicating the baseline level of students' narrative writing proficiency. Following the implementation of Writing Relay in the first cycle, the average posttest score significantly improved to 73.76, demonstrating a notable enhancement in students' narrative writing skills. Subsequently, in the second cycle, the average posttest score further increased to 80.91, indicating continued progress and development in students' writing capabilities. The findings of this study suggest that the implementation of Writing Relay as a teaching strategy effectively contributed to the improvement of students' writing skills in narrative text. The significant increase in students' posttest scores across the cycles indicates the positive impact of Writing Relay on enhancing students' narrative writing proficiency. The results highlight the importance of utilizing interactive and collaborative writing activities, such as Writing Relay, to engage students in the writing process and foster their creativity and storytelling abilities. This research provides valuable insights into the effectiveness of Writing Relay as an instructional approach to enhance students' narrative writing skills and offers implications for future teaching practices aimed at promoting students' proficiency in narrative text composition.